Strategic Management in Public Administration - Aghenitei, Mihaela (Journal of Danubian Studies and Research, 2022)
Strategic management is a way of setting strategy by public organizations that integrates strategy, and thus includes its planning to formulate new strategies, ways to integrate strategies, as well as continuous strategic study. This strategic management can support public organizations to achieve their very important objectives as well as to develop public value. This strategy is what unites the capabilities and aspirations of public organizations. There are four types of strategists, as individuals, teams, organizations or collaborations and in public administration, as in other situations: the reactor who has low desires, mediocre capabilities, the dreamer, who aspires to special results, with low capabilities, i.e. the one who does not achieves nothing, another who has low aspirations, quite high capabilities, being also a skilled strategist, leading to high aspirations and high capabilities. There are eight approaches to strategic planning. Broader process approaches include those influenced by the Harvard Policy Model, i.e. logical incrementalism and stakeholder management. Process approaches in a partial way include strategic negotiations, the management of these strategic issues as well as strategic planning as a framework for continuous innovation. Finally, there are also two background approaches, namely an analysis of the portfolio as well as of the forces inscribed in competition.